Effect of Gelugur (Garcinia atroviridis) Acid Juices on pH and Organoleptic Test of Quail (Coturnix coturnix japonica) Meat - Hutapea, Isron Nauli; Nurzainah Ginting; Usman Budi; M I Aja (Jurnal Peternakan Integratif, 2024)
Quail meat (Coturnix coturnix japonica) has high protein content, as well as low fat. This research aims to determine the effect of using gelugur tamarind juice on the physical quality and organoleptic quality of quail meat. The research was conducted in June-July 2024 at the Technology Research Laboratory, Faculty  of agriculture and Animal Production Laboratory, Faculty of Agriculture, Universitas  Sumatera Utara. The design used in this  research was a Completely Randomized Design (CRD) with 4 treatments and 5 replications, so in total there wewe 20 experimental units, namely T0=0ml, T1=30ml, T2=60ml and T3=90ml. The parameters used in this research are physical and quality tests, namely pH on quail meat, and organoleptic tests of color, aroma, taste and texture.The results  of this study showed that administration of gelugur acid juice 30ml, 60ml, 90ml had a very significant effect (P<0,01) on physical quality and organoleptic quality. The higher the percentage of gelugur acid assence used in quail meat, the greater the physical quality and organoleptic quality of the quail meat.